The Reliability of Energy Infrastructures; The Organizational Requirements of Technical Operations. Issue 2 (June 2013) - Scholten, Daniel
The reliable operation of energy infrastructures is more than just a technical matter. It is also dependent upon the organizational structure that enables and constrains entities in their management of operations. Yet while this lesson is well-known to scholars, there still exists a lack of understanding on how multiple actors should coordinate their actions to reliably operate energy infrastructures. In response, this paper proposes a framework that allows establishing the organizational structures required for the reliable operation of energy systems. The result is a stepwise progression that moves from the technical characteristics of energy infrastructures to the organizational structure required to facilitate reliable operations via identifying the critical technical functions and their accompanying control mechanisms and then establishing the responsibilities and coordination requirements that they imply for the entities involved in operations. The paper ends with a reflection on in how far we have achieved the intention and what still needs to be done.